Origin and migration mechanism of the main hydrocarbon seeps in western Greece - ΝΙΚΟΛΑΟΥ Κ. Α. (Bulletin of the Geological Society of Greece, 2001)
In this presentation a description of the main hydrocarbon indications of Western Greece is given, in relation to their origin and migration mechanism. Five groups of oil have been defined (Palacas et al.1986, Ν. Rigakis 1999) and their appearance on surface or in wells is explained. Doger shales are the source rocks of the first group of oil seeps in the central Ionian zone in Epirus (Botsara). Migration takes place through inverse or thrust faults. The second group is located at Trifos of Etoloakarnania, and Kyllini and West Katakolon well of NW Peloponissos. It is originated from Lower Cretaceous source rocks and migration happens through active diapiric movements of the Triassic evaporites. Triassic evaporites play important role in the maturation and migration and possible entrapment of this group of oil. The third group has genetic and migration relation with Triassic evaporites and their movements and is found at Delvinaki of Epirus and in the Well South Katakolon, offshore West Peloponissos. The fourth group that appears at Keri and Alikes of Zakynthos Island, it is possible to be originated from Middle- Upper Miocene post-tectonic sediments. The unconformity between Alpine and Post-Alpine sediments and some normal faults, is the possible pathway of migration mechanism. In the same team another oil show at Marathopolis, near Filiatra, is included with some doubts about its real origin. The fifth group is found at Paxos Island in the Preapulian zone. The oil is generated mainly from Middle-Upper Jurassic sediments, while older sediments of Lower Jurassic and Triassic are not excluded as possible source of the oil seeps. It is important to note that the contribution of the ground water movements is important in migration mechanism in some of the described cases. Finally, we strongly believe that the geological sections that are included in the text explain better our results and thoughts.